Clanis bilineata tsingtauica: A Sustainable Edible Insect Resource - Yu Gao (MDPI AG, 2021)
Insects provide a series of ecological services vital to human survival. Over 1000 insect species have been used for human consumption in Asia, Latin America, and Africa for more than 2000 years. Among them, the soybean hawkmoth, Clanis bilineata tsingtauica (CBT), is a traditional edible insect. CBT, known for its high nutritional value, is considered safe with a long consumption history in East Asia. The present review provides an overview of the rearing technology and utilization prospects of CBT. It has been extensively cultivated on live soybean plants under field and glasshouse conditions. However, an efficient rearing technology has not been reported. The mass production of CBT is still under investigation, and more advanced technology is required to develop high-quality food ingredients to meet consumer needs on a large scale. In addition, food derived from the soybean hawkmoth is prevalent in the farm product market. It is used as freeze-dried, fried, fresh meat, and canned meat. CBT-derived food, a potential dietary supplement used to retard aging in humans, would be a novel and emerging product in the food industry. The development of CBT-derived food will generate more economic and social value if the market demand can be met. This review will provide an insight into CBT mass production and its potential application in the food industry.